KEEFEKTIFAN MEDIA BELAJAR BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Baharudin, Rahmawati (STAIN Pamekasan, 2010)
Abstract : This article describes the existence of information, technology and communication-based media. It becomes an important element in the process of learning. Accelerating the development of information, technology and communication has given significant influences in the world of education. Learning media are presented in various formats and types. In practical terms, the effectiveness of information, technology and communication-based media for instruction depends on the ability and willingness of teachers. Therefore, teachers skills in using media and information, technology and communication-based learning are crucially necessary.